2017
DOI: 10.1002/jssc.201601261
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐performance convergence chromatography for the quantitative determination of bioactive compounds in Aralia continentalis Kitagawa as quality control markers

Abstract: A rapid ultra-performance convergence chromatography method was developed for the quantitative determination of bioactive compounds in Aralia continentalis as quality control markers. Quantitative analysis indicated the presence of two major bioactive compounds: diterpenoid acids continentalic acid and kaurenoic acid. Using a Torus 1-aminoanthracene column, continentalic acid and kaurenoic acid were separated in less than 8 min. The method was validated with respect to precision, accuracy, and linearity accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Back pressure and column temperature both influence mobile phase density and then influence the eluting power [18, 19]. As for back pressure, it directly influences the eluting power of a supercritical fluid through changing the density of CO 2 [20, 21].…”
Section: Resultsmentioning
confidence: 99%
“…Back pressure and column temperature both influence mobile phase density and then influence the eluting power [18, 19]. As for back pressure, it directly influences the eluting power of a supercritical fluid through changing the density of CO 2 [20, 21].…”
Section: Resultsmentioning
confidence: 99%
“…We speculated that the separation of Thl and Cal may be significantly affected by the polarity of mobile phase B and the polarity of mobile phase B is slightly larger or smaller, which is not conducive to the separation of the two isomers. It is noteworthy that the back pressure directly influences the eluting power of a supercritical fluid by changing the density of supercritical carbon dioxide [26]. Hence, different values of back pressure (1700, 1800, 2000, and 2500 psi) were investigated.…”
Section: Optimization Of Upc 2 Conditionsmentioning
confidence: 99%
“…More importantly, UPC 2 is an environmentally friendly analytical technique that employs dramatically reduced quantities of organic solvents compared to conventional chromatographic methods [23,24]. Nowadays, UPC 2 technology has been widely utilized in pharmaceutical analysis, and could serve as an alternative or complementary approach alongside HPLC and GC [25][26][27]. To the best of our knowledge, no studies have been reported on the use of UPC 2 for analyzing Thl and Cal in Thymi herba as QC markers.…”
Section: Introductionmentioning
confidence: 99%
“…Sci. 2021, 11, 7829 2 of 11 acid and benzoic acid) and monoterpenoids (albiflorin and paeoniflorin) from P. lactiflora, cardiac glycosides (neritaloside and odoroside H) from T. chinensis, miscellaneous (5-hydroxymethylfurfural) from R. alutinosa, phenylpropanoids (ferulic acid) and miscellaneous (senkyunolide A and (Z)-ligustilide) from C. officinale, triterpenoids (ginsenoside Rb1 and ginsenoside Rg1) from P. ginseng, triterpenoids (pachymic acid and polyporenic acid C) from P. cocos, steroids (ecdysterone) from A. bidentata, iridoids (geniposide and geniposidic acid) and lignans (pinoresinol diglucoside) from E. ulmoides, iridoids (gentiopicroside and loganic acid) from G. straminea, phenylpropanoids (methyleugenol and safrole) from A. heterotropoides, chromones (prim-O-glucosylcimifugin and 5-O-methylvisammioside) from S. divaricate, phenylpropanoids (cinnamic acid and cinnamaldehyde) from C. cassia, flavonoids (liquiritin and liquiritin apioside) and triterpenodis (glycyrrhizin) from G. uralensis, and phenols (6-gingerol and 6-shogaol) from Z. officinale [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%